Education and resistance testimonios for critical pedagogy and literacy - Moratilla, Noel Christian A. (2012)
The exploratory/theoretical essay discusses the potential of testimonios or testimonial narratives in critical pedagogy and literacy, especially as or when practiced in Third World/ Post-Colonial countries such as the Philippines. The discussion foregrounds the possibility of using testimonial narratives to underscore the dialectical connection between..
Keywords: Education -- Aspects; Critical pedagogy